Estrategias de poder utilizadas por los directivos de una institución educativa particular en postpandemia - Mamani Roman, Ruth (2023)
The study focuses on identifying which are the power strategies used by the directors of a particular institution under the gaze of the micropolitical approach. Therefore, the objective of this research is to describe the power strategies used by managers in a particular educational institution in the post-pandemic period. The present study is of a qualitative type, the technique and the instrument to be used was the semi-structured interview, which was applied to 3 directors of the institution who describe through anecdotes and particular events the power strategies they use to achieve the objectives of the organization. organization. Likewise, the interview was based on 2 categories: Communication strategies and coercive strategies. As general conclusions of the study, the 3 managers use the strategies based on the first category, communication strategies, such as: Horizontal treatment, dialogue, emotional support, empathy, flexibility, individual conversations, ingratation, logical arguments and negotiations.